Elasmobranchs observed in deepwaters (45-330m) at Isla del Coco National Park, Costa Rica (Eastern Tropical Pacific) - Cortés Núñez, Jorge (2012)
Isla del Coco is an oceanic island 500km off the Pacific coast of Costa Rica. It is a National Park and its marine fauna has been relatively well protected. The island is famous for its elasmobranch (sharks, rays and skates) sightings in shallow waters. Here we present a catalogue of the deepwater elasmobranchs observed with the DeepSee submersible. Five species of sharks, six species of skates and one ray have been observed between 45 and 330m depth. Triaenodon obesus, the white tip reef shark, was commonly observed between 80 and 301m, but only in the afternoons. Sphyrna lewini, the scalloped hammerhead shark, was observed as deep a 303m, but commonly between 45 and 90m, and close to the island. Odontaspis ferox, the smalltooth sand tiger shark, was observed between 82 and 316m. Echinorhinus cookei, the prickly shark, was observed between 91 and 320m. Rhincodon typus, the whale shark, was observed only close to the island, between 77 and 80m. Taeniura meyeni, the marbled ray, was observed only close to the island, between 45 and 90m. A Dasyatis sp., similar to the the diamond stingray, was observed only once close to the island at 60m; this is the first report of this genus at Isla del Coco National Park. Manta birostris, the giant manta, was only observed close to the island at 90m. Mobula tarapacana, the sicklefin devil ray, was observed between 60 and 326m, extending its maximum depth almost 10 times what has been reported. Aetobatus narinari, the spotted eagle ray, was observed only close to the island between 60 and 82m. Torpedo peruana, the Peruvian torpedo ray, was observed only once at 313m, and is the first record of this species from Isla del Coco National Park.